FLAIR vascular hyperintensities indicate slow poststenotic blood flow in ICA stenosis - Apfaltrer, Paul; Wenz, Holger; Böhme, Johannes; Gawlitza, Matthias; Groden, Christoph; Alonso, Angelika; Förster, Alex (Clinical neuroradiology, 2021)
Occlusion or significant stenosis of the internal carotid artery (ICA) in the cervical segment is commonly associated with a poststenotic decrease in the downstream blood flow and perfusion. Fluid attenuated inversion recovery (FLAIR) vascular hyperintensities (FVH) are a phenomenon that represents slow arterial blood flow. In this study, we investigated the frequency and extent of FVH in the distal ICA in patients with proximal ICA stenosis.
Gesehen am 04.10.2021
Published online: 31 August 2020